Cytoarchitectonic segregation of human posterior intraparietal and adjacent parieto-occipital sulcus and its relation to visuomotor and cognitive functions. (15th December 2018) - Richter, Monika; Amunts, Katrin; Mohlberg, Hartmut; Bludau, Sebastian; Eickhoff, Simon B; Zilles, Karl; Caspers, Svenja
Abstract: Human posterior intraparietal sulcus (pIPS) and adjacent posterior wall of parieto-occipital sulcus (POS) are functionally diverse, serving higher motor, visual and cognitive functions. Its microstructural basis, though, is still largely unknown. A similar or even more pronounced architectonical complexity, as described in monkeys, could be assumed. We cytoarchitectonically mapped the pIPS/POS in 10 human postmortem brains using an observer-independent, quantitative parcellation. 3D-probability maps were generated within MNI reference space and used for functional decoding and meta-analytic coactivation modeling based on the BrainMap database to decode the general structural–functional organization of the areas. Seven cytoarchitectonically distinct areas were identified: five within human pIPS, three on its lateral (hIP4-6) and two on its medial wall (hIP7-8); and two (hPO1, hOc6) in POS. Mediocaudal areas (hIP7, hPO1) were predominantly involved in visual processing, whereas laterorostral areas (hIP4-6, 8) were associated with higher cognitive functions, e.g. counting. This shift was mirrored by systematic changes in connectivity, from temporo-occipital to premotor and prefrontal cortex, and in cytoarchitecture, from prominent Layer IIIc pyramidal cells to homogeneous neuronal distribution. This architectonical mosaic within human pIPS/POS represents a structural basis of its functional and connectional heterogeneity. The new 3D-maps of the areas enable dedicated assessments of structure–function relationships.